OP28 What is the impact on health and wellbeing of interventions that foster respect and social inclusion in community-resident older adults? A systematic review of empirical studies. (13th September 2016) - Ronzi, S; Pope, D; Orton, L; Valtorta, NK; Bruce, N
Abstract : Background: Diminished respect and social inclusion may negatively impact on older people's health. Although many interventions promoting respect and social inclusion have been developed, the evidence of their impacts is unclear. This systematic review aimed to identify the effects of such interventions on the health of older people, as part of an empirical investigation of this topic in Liverpool. Methods: Eligible studies were identified by searching six bibliographic databases using a pre-piloted strategy, screening reference lists of retrieved items and searching organisational websites (January 1990 to January 2015). The study inclusion criteria were: included community-resident people aged 60+; measured the impact of an intervention to promote respect and social inclusion on physical/mental health; published in English. All study designs were eligible. Titles and abstracts, and full texts were screened for eligibility by one reviewer. A second reviewer independently screened a 10 percent random sample. One reviewer extracted data into standardised forms, and assessed the quality and risk of bias using the Liverpool University Quality Assessment Tool for quantitative studies, and an adapted version of a tool developed by Harden et al, and May and Pope for qualitative studies. Narrative synthesis of study findings was conducted as heterogeneity of interventions, outcomes and designs precluded meta-analysis. Results: Of 27, 354 records retrieved, 62 studies (31 quantitative, 9 qualitative, 22 mixed methods) met inclusion criteria. A broad range of interventions were identified, focusing on: mentoring; dancing; music/singing; art and culture; information-communication technology; intergenerational programmes. Most studies had high risk of bias, particularly regarding sample representativeness. Impacts were reported on a varied range of health outcomes. For example, music/singing improved mental health related quality of life and anxiety, dancing interventions improved balance and stability, and intergenerational interventions improved depressive symptoms/mood, quality of life, and wellbeing. Qualitative evidence enhanced understanding of health and psychological benefits of the interventions reported by older people, as standard outcome measures (e.g. depression scales) often failed to capture the nuanced effects of interventions. Conclusion: Whilst this review indicated that interventions on respect and social inclusion impact positively upon the health of older people, the included studies were heterogeneous and many had considerable risk of bias, which should be addressed in future studies. Many, though not all, of the interventions were delivered as projects to selected groups, raising important questions about feasibility and impact of wider implementation to secure population benefits. Key limitations included searches restricted to date and to English language.